Efeito da granulometria e da litologia no comportamento de lastros ferroviários em laboratório e por análise computacional - Rosa, André Fardin (2019)
The particle size distribution (PSD) and lithology of the ballast layer has huge influence on its behavior when subjected to the load generated by trains, being a key factor in the lifespan of the railway pavement. However, most of the specifications related to lithology and granulometric distributions for ballast provide unclear limits, covering materials with different behavior. Aiming at these aspects, this work analyzes the results of permanent deformation, resilience modulus and particle breakage in real scale, using a physical model and, in reduced scale, with cyclic triaxial and the use of parallel granulometries. The results of each parameters were analyzed together with the morphology and data from computational models using the Discrete Elements Method (DEM) and with the use of correlation tables to observe trends and relationships. Subsequently, more in-depth analyzes were carried out, comparing with results from the literature and adjusting mathematical models to the variables of interest. The adjustments made indicated a high correlation between parameters of the PSD, the permanent deformation and the particle breakage, for all the lithotypes analyzed. It was identified that the intermediate size fraction of the PSD governs the mechanisms of abrasion and chipping, for railroads with axle loads around 20 tf.